Candido Lima da Silva Dias: da Politécnica aos primórdios da FFCL da USP - Duarte, Paulo César Xavier [UNESP] (2014)
This thesis highlights the professional history of Professor Candido Lima da Silva Dias, emphasizing his role as a mathematics professor since being the assistant of the Italian Professor Luigi Fantappiè and as a professor of the newly created Faculdade de Filosofia Ciências e Letras da Universidade de São Paulo – FFCL from USP, in 1934. Thus, the aim of this research is to analyse the transfer of Candido Lima da Silva Dias, from the Politécnica to FFCL of USP, investigating his academic work in this college. For achieving this aim, firstly the preliminary considerations are worked, the USP FFCL foundation is highlighted, moreover it will be developed research methodology topics used in this thesis, for instance biographies, documents, and acquis. It will be mentioned the Escola Politecnica historic facts such as the foundation aspects and its initial teaching programs. Morever it will be emphasized the history of Candido Dias as a mathematics professor in the beginning of USP FFCL. For this goal, it will be revealed general aspects of the mathematics teaching – worked by Professor Candido Dias with the aim to observe the methodology and teaching aspects used in his career while being a USP FFCL professor since 1930s decade until the beginning of 1950s decade. As a result, it will be pointed out his Doctorate thesis about The Regularity of the defined functionals in the analytical functions, and also his scientific and teaching activities as well as his published work – done using his own documents stored by Candido Dias himself and kindly provided for research by his family